Detection of water pathogen based on dielectrophoresis - Chow, Kun Shyong (2012)
A neutral particle is polarized when it is subjected to non-uniform electric field, and upon polarization, this neutral particle will be moved by dielectrophoretic force. Neutral particles include polystyrene bead, cells, bacteria and other micro-organisms. By utilizing dielectrophoretic phenomena, separation of cells and bacteria can be achieved instantly and this separation method was proven to be effective by previous researchers. Compared to other conventional clinical separation methods, the dielectrophoresis (DEP) separation can greatly reduce the experimental cost and time.